222k views
4 votes
Step by Step Explanation Please

Step by Step Explanation Please-example-1
User Shrhawk
by
4.6k points

2 Answers

5 votes

Answer:

F(4)= -18

G(-3)=-76

f(x)= -5x+2

g(x)=3x^3+5

To find f(4), wherever you see x in f(x) put in 4

-5(4)+2= -18

To find g(-3), wherever you see x in g(x) put -3

3(-3)^3 +5= -76

User Parapluie
by
5.3k points
5 votes

f(4) = -18

g(-3) = -76

Explanation:

f(x) = -5x + 2

f(4) = -5(4) + 2

= -20 + 2

= -18

g(x) = 3x^3 + 5

g(-3) = 3(-3)^3 + 5

= 3(-27) + 5

= -81 + 5

= -76

User Sajjan Sarkar
by
5.1k points